Donor funding for newborn survival: an analysis of donor-reported data, 2002-2010. - Catherine Pitt; Joy E Lawn; Meghna Ranganathan; Anne Mills; Kara Hanson (PLoS Medicine)
Background Neonatal mortality accounts for 43% of global under-five deaths and is decreasing more slowly than maternal or child mortality. Donor funding has increased for maternal, newborn, and child health (MNCH), but no analysis to date has disaggregated aid for newborns. We evaluated if and how aid flows for newborn care can be tracked, examined changes in the last decade, and considered methodological implications for tracking funding for specific population groups or diseases. Methods and findings We critically reviewed and categorised previous analyses of aid to specific populations, diseases, or types of activities. We then developed and refined key terms related to newborn survival in seven languages and searched titles and descriptions of donor disbursement records in the Organisation for Economic Co-operation and Development's Creditor Reporting System database, 2002-2010. We compared results with the Countdown to 2015 database of aid for MNCH (2003-2008) and the search strategy used by the Institute for Health Metrics and Evaluation. Prior to 2005, key terms related to newborns were rare in disbursement records but their frequency increased markedly thereafter. Only two mentions were found of "stillbirth" and only nine references were found to "fetus" in any spelling variant or language. The total value of non-research disbursements mentioning any newborn search terms rose from US$38.4 million in 2002 to US$717.1 million in 2010 (constant 2010 US$). The value of non-research projects exclusively benefitting newborns fluctuated somewhat but remained low, at US$5.7 million in 2010. The United States and the United Nations Children's Fund (UNICEF) provided the largest value of non-research funding mentioning and exclusively benefitting newborns, respectively. Conclusions Donor attention to newborn survival has increased since 2002, but it appears unlikely that donor aid is commensurate with the 3.0 million newborn deaths and 2.7 million stillbirths each year. We recommend that those tracking funding for other specific population groups, diseases, or activities consider a key term search approach in the Creditor Reporting System along with a detailed review of their data, but that they develop their search terms and interpretations carefully, taking into account the limitations described. Please see later in the article for the Editors' Summary.